Energy efficiency improvement by using hygrothermal diagnostics algorithm for historical religious buildings. (1st August 2022) - Fedorczak-Cisak, Małgorzata; Radziszewska-Zielina, Elżbieta; Białkiewicz, Andrzej; Prociak, Aleksander; Steidl, Tomasz; Tatara, Tadeusz; Żychowska, Maria; Muniak, Damian Piotr
Abstract: Improving the energy quality and performance of historic buildings is a complicated task, both from the research, design and executive point of view. The aim of this paper and the main motivation of the authors was to improve the energy quality and energy performance of one of the building partitions of a historic church in terms of not deteriorating both the technical condition of the element to be modernised, and maintaining an interior microclimate appropriate for such objects. The authors hypothesised that the algorithm proposed should contain both typical tests as well as modern diagnostic and simulation methods that allow to predict the results of the impact of the planned changes on historic elements. The conclusions confirmed that the use of the proposed research methods allows for the simultaneous improvement of energy performance and the preservation of historic elements, and preventing the deterioration of the specific microclimate of the building. With such measures, it was possible to reduce the annual heat demand indicator for heating the building from 253.73 [kWh/(m 2 y)] to 77.59 [kWh/(m 2 y)] constituting about 69%. Highlights: A new methodology for assessing and improving partition energy indicators has been presented. The methodology assumes no negative impact on the condition of partitions and indoor climate. Calculations and measurements were made on the basis of "in situ" studies of an actual indoor climate. The methodology is useful for the non-invasive assessment of the energy indicators of partitions. Nearly 70% energy saving while preserving microclimate and historic elements.